Surgical Management of Fetal Maceration in a Bitch - Kumar, Vinod; Sharma, Keshav; Narwade, Priyanka; Jena, Dayanidhi (The Indian Journal of Animal Reproduction, 2025)
A 7-year-old intact bitch was presented with a history of foul smelling serosanguinous vaginal discharge and in-appe tence since the last 15 days. Radiographic examination revealed radiopaque structures resembling scattered bony masses. Based on the history, clinical findings and radiographic analysis the case was suspected for fetal maceration and it was immediately referred for surgical intervention. Three macerated fetal masses were removed. The detailed clinical exam ination, diagnosis and surgical treatment is discussed.